Use of fiberglass CAD-CAM post-and-core for rapid orthodontic extrusion of anterior tooth – Case Report (Research, Society and Development, 2021)
This report describes the restoration of an anterior fractured tooth with a fiberglass CAD-CAM post-and-core followed by rapid orthodontic extrusion. The post space was prepared, the post-and-core was luted and a interim crown was luted to allow the tooth extrusion through the use of orthodontic buttons and elastic rubber bands. A lithium disilicate glass-ceramic crown was luted and the case was followed up after 6 and 12 months.